Cover cropping in rainfed fruticulture - Rodrigues, M.A. (2020)
A significant part of the world’s fruticulture is rainfed managed. Olive, almond and vine are some of the perennial crops whose social and economic importance is huge throughout the Mediterranean basin and which mostly continue to be grown in rainfed conditions. Cover cropping is the most recommended soil management system in fruit growing. However, in rainfed managed orchards, soil tillage continues to dominate, and the use of herbicides is also widely used. In rainfed conditions there is a high risk of competition for water between herbaceous vegetation and trees, which makes difficult the widespread use of cover crops. However, there seem to be new clues to overcoming the problem, consisting of the use of less competitive plants, such as early-maturing self-reseeding annual legumes. These plants are able to protect the soil from erosion, sequester carbon and increase soil organic matter, fix nitrogen and promote the nutritional status of the trees and fruit yield. Their growing cycles finish early in spring which greatly reduces the competition for water.